Emotion Framework in Leadership Programs for TVET and Higher Education Students - Ahmad, Zaiha; Ibrahim, Zuraeda; Ibrahim, Nordiana; Azmi, Nur Nafishah; Zakir, Supratman; Mohd Lokman, Anitawati (Journal of Technical Education and Training, 2024)
Recent research has highlighted the significant impact of emotions on learning outcomes, particularly in education. However, discussions on effective student leadership programmes often neglect the emotional dimension, hindering the holistic development of future leaders. To address this gap, this study explores the intricate link between emotions and programme design, focusing on increasing student awareness and sensitivity. Conducted in Malaysian higher education, the research aims to establish an emotion framework for student leadership programme. Using the KJ Method with 30 participants and Quantitative Kansei Engineering involving 120 students, the study identifies 28 emotional clusters, with "excitement" and "confidence" as central structures. The "excitement" cluster encompasses emotions like "motivating," "joyful," and "energetic," while the "confidence" cluster includes emotions such as "confident," "challenging," and "determined." The analysis on factor and principal component loadings results in a Framework of Emotion in Student Leadership Programs. This framework underscores the significance of integrating and nurturing a harmonious interaction between emotional elements in programme design, with "excitement" and "confidence" as fundamental pillars. By incorporating emotional responses into the design process, an environment that elicits excitement and confidence among students can be created. These findings not only contribute to successful leadership program designs but also extend to other educational contexts. In the realm of Technical and Vocational Education and Training (TVET), these insights are particularly relevant. Like student leadership programs, TVET requires a holistic approach that integrates the emotional dimension of learning. Such a balanced approach fosters emotional intelligence alongside technical skills, thereby enhancing student engagement and learning outcomes.